2016
DOI: 10.1007/s10891-016-1424-6
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Vortex Structures in the Prenozzle Space of an Engine with a Vectorable Thrust Nozzle

Abstract: A numerical simulation of the hydrodynamic effects arising in the process of work of the vectorable thrust nozzle of a solid-propellant rocket engine has been performed. The fi elds of the fl ows of combustion products in the channel of a charge, the prenozzle space, and the nozzle unit were calculated for different angles of vectoring of the nozzle. The distributions of the gasdynamic parameters of the fl ow of combustion products in the prenozzle space, corresponding to their effl ux from the cylindrical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Mathematical modeling of intrachamber processes in a power plant is considered in [14][15][16][17][18][19][20][21]. However, they lack practically useful criteria equations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mathematical modeling of intrachamber processes in a power plant is considered in [14][15][16][17][18][19][20][21]. However, they lack practically useful criteria equations.…”
Section: Introductionmentioning
confidence: 99%
“…However, they lack practically useful criteria equations. In [13][14][15][16][17][18][19][20], it is shown that the spatial flow in the CC and PV is characterized by the presence of vortex structures. Heat exchange processes in different layouts of PP are studied in [15][16][17], but they do not provide criteria relations, and there is no assessment of the applicability for equations [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For technological reasons, the subsonic part of the rotary nozzle is usually submerged into the combustion chamber (submerged nozzle). The immersion of the nozzle inside the pre-nozzle volume reduces the longitudinal size of the rocket, but generates a number of problems associated with the high-temperature flow of combustion products [7][8][9]. In a submerged nozzle, the impact of a two-phase flow of combustion products hits the frontal surface of the nozzle inlet, which poses the problem of organizing the flow in this area, excluding increased thermal and erosion effects [2].…”
Section: Introductionmentioning
confidence: 99%